2022
DOI: 10.7441/joc.2022.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Competitiveness in the Supply Chain Management of Small and Medium Scale Enterprises

Abstract: This research investigated Supply Chain Management (SCM) in Small and Medium Enterprises (SMEs) in Thailand, Slovakia, and Poland and compared the SCM practices among the three countries. The sole purpose was to first determine the various factors that influence SCM operations and SCM practices in each of the countries and then find out whether there is a difference among the three countries in terms of SCM operations and practices. The study was conducted using primary data collected from SME management perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…The measurement model was used to determine the relationship between the latent variables (constructs) and the observed variables (indicators). The structural model was applied to determine the causal relationship between the latent variables (Chin et al, 2003;Muangmee et al, 2022). The multi-group analysis evaluated the difference between Thailand and Poland regarding the determinants of AI-based applications adoption in the agricultural sector.…”
Section: Methodsmentioning
confidence: 99%
“…The measurement model was used to determine the relationship between the latent variables (constructs) and the observed variables (indicators). The structural model was applied to determine the causal relationship between the latent variables (Chin et al, 2003;Muangmee et al, 2022). The multi-group analysis evaluated the difference between Thailand and Poland regarding the determinants of AI-based applications adoption in the agricultural sector.…”
Section: Methodsmentioning
confidence: 99%
“…Certainly, the effects of globalization have influenced the full range of administrative activities and processes associated with the flow of goods and services to end users (Hult, 2004;Mudambi and Venzin, 2010). According to Muangmee et al (2022), the concept of SCM involves the effective management of the supply chain activities, including product development, sourcing, production, and operations, and managing the supply in organizations (Zimon et al, 2020). Equally important, SCM aims at the movement of goods and services from one end of the supply chain to the other, through different stages to improve efficiency, productivity, and the profitability of the entire process (Seth et al, 2015).…”
Section: Preliminary Notesmentioning
confidence: 99%
“…In addition, the SCM practice involves the activities and actions employed by SMEs towards promoting their business supply chains. Certainly, something that add significant value to the customers is precisely the SCM practices to provide products, services, and information (Muangmee et al, 2022). In fact, Monnagaaratwe & Motatsa (2021) consider that the adoption of SCM initiatives by corporations has been one of the key business strategies, which has resulted in companies to follow customer-centric approach in their operation to satisfy customer requirements.…”
Section: Preliminary Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to keep in mind that every global event brings with it both new opportunities and threats that can potentially affect the management of global supply chains (Kot et al, 2020). For the most part, companies are well aware of the definitions of supply chain risk management (Muangmee et al, 2022), however, recent events have shown that this knowledge is purely theoretical and in many cases focused only on their company or the closest links in its supply chain.…”
Section: Introductionmentioning
confidence: 99%